Phagocytic activity of blood monocytes and neutrophils in moderate COVID-19 patients and impact of immune therapy with bacterial lysates - Mikhail Kostinov; Oksana Svitich; Alexander Chuchalin; Viliya Gajnitdinova; Irina Bisheva; Svetlana Skhodova; Valerij Osiptsov; Vitalij Tatevosov; Nadezhda Kryukova; Isabella Khrapunova; Alexander Cherdantsev; Irina Soloveva; et al. (PLoS ONE, 2025)
Background Monocytes, macrophages and dendritic cells are involved in phagocytic reactions, which potentially play an important role in the pathogenesis of COVID-19. Imbalance of these cells in peripheral blood has proven to affect not only innate but also adaptive immunity. It is possible that a search for strategies to restore monocyte activity could be a major step in achieving immune control over COVID-19. The aim of this study was to investigate the relationship between phagocytic activity of peripheral-blood monocytes and neutrophils, and COVID-19 severity, to assess the effects of a bacteria-based immunostimulating agent on phagocytosis parameters in in-hospital COVID-19 patients. Materials and methods The study included 105 adult patients with moderate COVID-19, who had been hospitalized in 2020–2021 and treated in accordance with the recommendations of the Ministry of Health of the Russian Federation. All patients were divided into two groups: in Group 1 patients received standard treatment and Immunovac VP4 therapeutic vaccine, a bacteria-based immunostimulating agent as add-on therapy from Day 1 of hospitalization; in Group 2 patients did not receive any add-on treatment. The study parameters included C-reactive protein (CRP), aspartate aminotransferase (AST), SpO2, lung involvement on chest computer tomography (CT) scan, and phagocytic activity of peripheral-blood leukocytes based on the absorption activity (AA) of monocytes and neutrophilic granulocytes against S. аureus). The parameters were assessed at 1, 14 and 30 days. Results Based on a cluster analysis of the clinical findings and the results of diagnostic tests obtained on admission, the patients were divided into 2 clusters: cluster 1 including patients with a more severe disease (n = 34) and cluster 2 including patients with a less severe disease (n = 71). Cluster 1 patients had higher levels of CRP (20.1 vs. 2.2 mg/mL, p < 0.001), AST (32.9 vs. 26.2 U/L, p = 0.003), lower SpO2 (94% vs. 96%, p < 0,001) and more extensive lung involvement on chest CT scan (35% vs. 12%, p < 0,001). There was a statistically significant direct correlation between blood monocyte AA and SpO2 (p = 0.04), an inverse correlation between monocyte AA and CRP (p = 0.003) and the extent of lung involvement on CT scan (p = 0.05). In less severe COVID-19 patients (cluster 2), no statistically significant correlation was observed. In more severe COVID-19 patients (cluster 1), there was a rise in monocyte AA on day 30 of hospitalization both in the control group (from 86.6 to 92.2, p = 0.03) and the main group, who received Immunovac VP4 add-on therapy (from 87.3 to 98.3, p = 0.05). However, the patients who received the immunostimulating agent, had higher monocyte PI than the controls, without the immunostimulant (p = 0.05). Patients from cluster 1 who were given Immunovac VP4 had higher SpO2 levels (98% vs. 97%, p = 0.01) than those who had received only the standard treatment. Discussion Blood monocyte AA correlates with COVID-19 severity: patients with less severe disease have higher AA and those with more severe illness have lower AA. The standard treatment, combined with Immunovac VP4 enhances phagocytic activity of peripheral-blood monocytes, which is associated with a more marked increase in SpO2, especially in more severe patients.